The paradoxes of the liberal ethics of non-interference - Marco Mariotti; Roberto Veneziani (Queen Mary University of London, Department of Economics, 2009)
We analyse the liberal ethics of non-interference applied to social choice. Two liberal principles capturing non-interfering views of society, inspired by J.S. Mill's conception of liberty are examined, which capture the idea that society should not penalise agents after changes in their situation that do not affect others. Two paradoxes of liberal approaches are highlighted. First, it is shown that a restricted view of non-interference, as reflected in the Individual Damage Principle, together with some standard axioms in social choice leads straight to welfare egalitarianism. Second, it is proved that every weakly paretian social welfare ordering that satisfies a general principle of noninterference must be dictatorial. Both paradoxes raise important issues for liberal approaches in social choice and political philosophy.
Keywords: D63; 330; liberalism; noninterference; equality; impossibility; Soziale Wohlfahrtsfunktion; Soziale Beziehungen; Soziale Ungleichheit; Liberalismus; Wirtschaftsphilosophie